Knowledge translation platforms: Broker, intermediary or more? A scoping review of definitions, functions and characteristics - Schmidt, B.; Mulopo, C.; Mayieka, L.; Cooper, S.; Jaca, A; Späth, C.; Oliver, J.; Jessani, N. S. (Health research policy and systems, 2025)
Background Knowledge translation platforms (KTPs), also referred to as intermediaries, play a key role in supporting evidence-informed decision-making. Numerous KTPs exist globally, striving to translate evidence into policy. However, these platforms are described in varying ways, and some KTPs do not explicitly identify themselves as such. This makes identification, recognition and leveraging of KTPs suboptimal. It also hinders opportunities for learning, adapting and scaling of such platforms. Objective This scoping review aimed to synthesize the literature on the variety of definitions, functions and characteristics of a KTP with a view to harmonize these aspects of KTPs and offer a revised framework of functions. Methods This review was conducted using recommended methods and reporting guidelines. Searches were performed in PubMed, Scopus and Cumulative Index to Nursing and Allied Health Literature (CINAHL) using a predetermined search strategy, without date or geographical restrictions. Included studies were analysed and synthesized in ATLAS.ti, following Braun and Clarke’s six steps of thematic analysis. Findings With one exception, all KTPs did not identify themselves as such in their names. Five common elements emerged across the KTP definitions: (i) a physical or virtual platform (ii) that engages with and convenes different stakeholders (iii) through a set of knowledge translation activities and outputs (iv) to contribute to health decision-making. We identified KTP activities that aligned with the core functions described in the Valmeekanathan et al. (Valmeekanathan et al. in Tert Educ Manag 27:227–256, 2021) framework – namely knowledge exchange, dialogue and capacity – but also additional activities, including engaging funders, planning for sustainability and scalability, providing training grants and initiating innovative knowledge translation processes that integrate knowledge across projects and sectors to maximize impact. Conclusion This review provides a synthesized definition of KTPs while expanding on the three core functions described in the Valmeekanathan et al. (Valmeekanathan et al. in Tert Educ Manag 27:227–256, 2021) framework. To maximize their impact, sustained investment, stronger institutional support and integration into national policy ecosystems are essential.